High Clonality and Geographically Separated Cryptic Lineages in the Threatened Temperate Coral, Acropora pruinosa - Pipithkul, Supisara; Ishizu, Sota; Shimura, Akifumi; Yokochi, Hiroyuki; Nagai, Satoshi; Fukami, Hironobu; Yasuda, Nina (Frontiers in Marine Science, 2021)
Acropora pruinosa is a threatened zooxanthellate scleractinian coral that is distributed in the temperate areas along the coastline of Japan and the northern area of the South China Sea. Since A. pruinosa propagates both asexually and sexually, assessing clonal diversity and genetic connectivity among populations is important for conservation. In addition, high morphological variations in the field create confusion during species identification. To examine the existence of hidden genetic lineages, clonality, and genetic connectivity of A. pruinosa for conservation, we applied microsatellite analysis. Clustering analysis indicated two distinct geographically separated genetic lineages: one is distributed in the west, and the other is distributed in the east. The two lineages co-existed in Nishidomari, Kochi. There was no obvious difference in morphological characteristics between the two lineages. Although the factors influencing the observed distribution patterns remain unknown, there is a possibility that the two lineages might have diverged somewhere in the north-western Kyushu and north-eastern Pacific coast habitats in the past, and then periodically colonized the current habitats. A low clonal diversity was observed in most of the populations, indicating a high rate of asexual reproduction associated with their branching morphologies. In addition, there are strong genetic structuring in this species, indicating weak connectivity among populations. These results indicated a low larval dispersal potential among populations and that populations are basically sustained by a high rate of clone propagation and self-seeding. The existence of cryptic lineages and genetically isolated populations with high clonality emphasized the importance of conservation of A. pruinosa.